Effects of Three Different Doses of Dexmedetomidine and Ropivacaine on Analgesia and the Stress Response in Hypospadias Surgery: A Randomized Trial - Yuan Wang; Ying-Ping Jia; Li-Yuan Zhao; Qiu-Juan He; Jin-Lian Qi; Rui Zhou; Ting Yang; Zeng-Xiao Zhao; Hao-Quan Wei (Frontiers Media S.A., 2021)
Objective: This study was designed to investigate the effects of three different doses of dexmedetomidine in caudal blocks on postoperative stress and pain after pediatric urethroplasty.Methods: A total of 160 children who underwent elective urethroplasty were enrolled in this study. They were randomly divided into four groups: groups D1, D2, and D3, in which the patients were injected respectively with a mixed solution of 1, 1.5, or 2 μg kg−1 of dexmedetomidine and 0.25% ropivacaine into the sacral canal; and group R, in which the patients were injected with 0.25% ropivacaine into the sacral canal. Cortisol and interleukin-6 (IL-6) levels within 24 h, the incidence of adverse events in the circulatory system during surgery, onset time of the caudal block, duration of postoperative analgesia, the incidence of agitation during recovery, and other anesthetic adverse reactions were observed and recorded.Results: Compared with group R, cortisol and IL-6 levels in groups D1, D2, and D3 decreased within 24 h after the operation (T2-T6). The incidence of intraoperative hypertension, tachycardia, and shivering during the recovery period decreased, the onset time of the caudal block decreased, and the duration of postoperative analgesia increased (p < 0.01). Compared with group D1, the duration of postoperative analgesia increased in groups D2 and D3 (p < 0.01). Compared with groups D1 and D2, the incidence of excessive sedation and bradycardia in group D3 increased (p < 0.05).Conclusion: The administration of 1.5 μg kg−1 of dexmedetomidine appears to be most feasible in accelerating the onset of the caudal block, reducing stress and inflammation, stabilizing the circulation, increasing the duration of postoperative analgesia, and reducing anesthesia- and operation-associated adverse events.